Idârah al-Tan?îm Libarnâmij Ta’lîm al-Lughah al-‘Arabiyyah bi Ma’had Tursîna al-Islâmî al-‘Alamî bi Mâlang (IIBS) - Lailatus Sholehah; Laily Fitriani; Akhmad Muzakki (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2021)
Purpose-This study aims to 1) describe the organizational management of the TAC program at Thursina IIBS Malang, and 2) the division of tasks in the management of the TAC program at Thursina IIBS Malang. Design/Methodology/Approach-This study uses a descriptive qualitative research method which was carried out on the TAC program at Thursina IIBS Malang. The data was collected by using interview, observation and documentation techniques. Data collection is done by reducing data, presenting or presenting data, and drawing conclusions. Data analysis using Miles and Hubberman technique with 1) Data reduction, 2) Data presentation, 3) Data verification. Findings-The results of the study explain that good organizational management is one of the factors for the success of students in learning Arabic, this is evidenced by the large number of Thursina students who have won several Arabic language competitions at the national or even international level. Research Limitation/Implications-This research cannot deepen research on several Arabic language learning program activities in Thursina, because basically there are several Arabic language learning programs that are not enforced temporarily in the midst of the covid'19 pandemic. However, the organizational management of the Arabic language learning program in Thursina can be said to be good and orderly because of the clear structure and the division of tasks in each division in the structure. Because with this clear structure, there is no overlap between one individual and another in carrying out the duties of each individual.